Numerical modeling of heat transfer and fluid motion in air gap between clothing and human body: Effect of air gap orientation and body movement. (May 2017) - Udayraj,; Talukdar, Prabal; Das, Apurba; Alagirusamy, Ramasamy
Highlights: A more accurate numerical model is proposed for heat transfer through air gap. Effect of horizontal and vertical air gap orientations are analyzed on heat transfer. Thermal protection found higher for vertical orientation as compared to horizontal. Effect of body motion is also analyzed on heat transfer through air gap. Motion frequency and average air gap width plays crucial role during body motion. Abstract: Air gap available between the clothing and human body provides significant thermal insulation and hence enhances the protective performance of clothing. A numerical model of fluid motion and heat transfer through the air gap is proposed in this work. The most realistic and detailed model considered in this work shows better accuracy than the previous models and brings several new insights to the combined heat transfer phenomena. Effect of horizontal and vertical air gap orientations on sensor temperature rise, heat flux, thermal protection and fluid flow behavior are analyzed. Results shows that thermal protection with the vertical air gap orientation is significantly better than the protection offered by the horizontal air gap orientation and the difference increases as the air gap width increases. Dynamic mesh technique is used in order to investigate the effect of dynamic air gap which results because of the body movement during heat exposure. Body movement is considered to be such that variation of the air gap with time is sinusoidal. Effect of motion frequency and average air gap width are also studied. Significant difference in convective and total heat flux as well as flow pattern is observed for cases with dynamically varying air gap.